Orthoptera of Northeast Asia and Northwest America - Storozhenko, Sergey Yu. (Zootaxa, 2023)
An annotated list of 42 species in 26 genera and four families of Orthoptera recorded from Beringia (Northeast Yakutia, Chukotka, Magadan region, and Kamchatka in Russia, Alaska in USA, Yukon and the Northwestern Territories in Canada) is given. The distribution of species is clarified. The exchange of orthopteran faunas between Asia and America by the Bering Land Bridge in Pleistocene was strongly limited. The only three species, Tetrix subulata (Linnaeus, 1761), Melanoplus frigidus (Boheman, 1846), and Stethophyma grossum (Linnaeus, 1758), are recorded from both Asian and American parts. The orthopteran fauna of Beringia is not original. Majority of Beringian species are widespread throughout either Asia or North America. There are only four endemic grasshoppers, namely two Asian subspesies, Melanoplus frigidus kamtchatkae (Sjosted, 1935) and Aeropedellus variegatus gelidus Mistshenko, 1951, and two American species, A. arcticus Hebard, 1935 and Bruneria yukonensis Vickery, 1969. Composition of the regional faunas is briefly discussed. The monotypic genus Bohemanella Ramme, 1951 is again considered as a synonym of Melanoplus Stål, 1873, where a type species of the former genus, Melanoplus frigidus (Boheman, 1846) comb. resurr., forming its own species group.